Liquid phase separation in transition element high entropy alloys. (July 2017) - Munitz, A.; Kaufman, M.J.; Abbaschian, R.
Abstract: Non-consumable arc melting was used to produce buttons of transition metal (Co-Cu-Fe) high entropy alloys (HEAs) with additions of Al, Cr, Mn, Ni, V or Ti. High resolution scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS) capabilities were used for microstructural characterization. It was found that certain HEAs exhibit stable liquid miscibility gaps causing separation into two liquids, namely a Cu-lean liquid, L1, and a Cu-rich liquid, L2. Since, in stable liquid phase separation (LPS) involving Cu, the Cu-rich L2 has a higher density and a lower melting temperature, it sinks to the bottom of the casting. Secondary melt separation was also observed and resulted in small spheres of the minority liquid embedded in the matrix of the first liquid. Additions of Co, Al, Ti, and Ni were found to lower the miscibility gap temperature (TMG ), while additions of Cr, V, and Nb were observed to raise TMG and enhance stable LPS. Thermodynamic calculations were used to support the experimental results. Highlights: HEAs exhibiting stable Liquid phase separation, LPS, separate into two liquids: a Cu lean liquid, L1, and a Cu rich liquid, L2. Characteristic microstructure of LPS is spheres of the minority liquid embedded in the microstructure of the other liquid. Secondary melt separation. Addition of Co, Al, Ti and Ni to the HEA liquid will lower the miscibility gap temperature. Addition of Cr, V, and Nb to the HEA liquid will raise the miscibility gap temperature.